Analyzing the Impact of Welfare Measures on Job Performance and Job Satisfaction of the Teachers - Kaur , Rupinder (Mathematical Statistician and Engineering Applications, 2023)
The research discussed factors including working conditions and fringe benefits that are part of welfare management methods that have an impact on teachers' job performance. Research hypotheses were used to direct the investigation. Employees are greatly inspired by welfare reforms, which contributes to the expansion of businesses. There is a close link between employee morale and job satisfaction, making welfare measurements an important component in both. The purpose of this research is to examine and assess existing worker protections and benefits. The survey, which gauges the effect on morale, draws the conclusion that most employees were happy with the welfare measures offered by the government, non-governmental institutions, and labor unions. A statistically significant and beneficial influence of working conditions on teachers' job performance was found, among other things, in the analysis of the replies. It has been suggested that the Calicut Education Service (CES) and individual schools implement rules that are supportive of teachers' families, improve working conditions, and guarantee timely payment of benefits.